Texte, trame, signe : les ficelles de l’art selon Dante Gabriel Rossetti - Laurence Roussillon-Constanty (Cahiers Victoriens et Edouardiens)
In the gallery of Dante Gabriel Rossetti’s so-called “double works of art”, Proserpina has often been singled out as the artist’s masterpiece. The aim of this article is to question or reassert this view by uncovering the Dantean subtext that informs the 1874 version of the painting and deciphering the coded message it contains. The point is to show that beyond the personal context of its creation and through the model of Dante’s Divine Comedy, Rossetti is pushing the limits of both forms of art—painting and poetry—thereby creating a new aesthetics where text and image merge into a musical form, where the work of art is an endless dialogue of the soul with itself.